2019
DOI: 10.1101/650952
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Population-based neuroimaging reveals traces of childbirth in the maternal brain

Abstract: 1Pregnancy and childbirth involve maternal brain adaptations that promote attachment to and protection 2 of the newborn. Using brain imaging and machine learning, we provide evidence for a positive relation-3 ship between number of childbirths and a 'younger-looking' brain in 12,021 women, which could not be 4 explained by common genetic variation. The findings demonstrate that parity can be linked to brain 5 health later in life. 6 Page 2 of 23Population-based neuroimaging reveals traces of childbirth in the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
88
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 39 publications
(103 citation statements)
references
References 41 publications
14
88
1
Order By: Relevance
“…Higher estrogen levels during menopause were as-sociated with higher brain age gap in carriers and lower brain age gap in non-carriers. Two main conclusions can be drawn from the results: I) In light of our recent findings showing a link between parity and lower brain age relative to chronological age (49), estrogen exposure and parity may differentially relate to brain aging; II) The genotype-specific associations between age at onset and dosage of HRT and brain aging suggest that genetic factors are important to consider in clinical settings.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Higher estrogen levels during menopause were as-sociated with higher brain age gap in carriers and lower brain age gap in non-carriers. Two main conclusions can be drawn from the results: I) In light of our recent findings showing a link between parity and lower brain age relative to chronological age (49), estrogen exposure and parity may differentially relate to brain aging; II) The genotype-specific associations between age at onset and dosage of HRT and brain aging suggest that genetic factors are important to consider in clinical settings.…”
Section: Discussionmentioning
confidence: 83%
“…Parous women may also have shorter menstrual cycles and lower levels of estradiol than nulliparous women (44,45), indicating that age at first birth also influences lifetime estrogen exposure. Studies have demonstrated a protective effect of parity on brain aging (31,(46)(47)(48), and we recently showed lower brain age in parous compared to nulliparous women in the UK Biobank cohort (49). In the present paper, we investigate the association between estrogen exposure and brain aging beyond the effects of parity.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations